Pengaruh Persentase Saham Dan Akuntansi Konservatisme Terhadap Relevansi Nilai Laporan Keuangan Dengan Kualitas Laba Sebagai Variabel Moderasi - Roy Alpinus Ginting; Lamria Simamora; M. Ichsan Diarsyad; Sri Yuni; Agus Kubertein; Iwan Christian (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of share percentage, accounting conservatism, the interaction of earnings quality and share percentage on value relevance and the interaction of earnings quality and accounting conservatism on value relevance in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The number of manufacturing companies used as samples in this study were 96 companies after going through the purposive sampling method. The results showed that partially the variable percentage of shares has no effect on value relevance, accounting conservatism has no effect on value relevance, earnings quality interactions are proven to be unable to moderate the relationship between share percentage to value relevance and earnings quality interactions are proven to be unable to moderate the relationship between accounting conservatism and relevance. Companies are expected to see the importance of other factors that can increase the relevance of the value of financial statements optimally. For investors, it is hoped that this can be used as input in making investment decisions in the future, before deciding to invest in the company. For further research, it is hoped that by adding other variables that might be able to predict the value relevance of financial statements even better.